Simulation and Experimentation Study of Mass Flow Rate in The Vortex Flow Metre - Juzly, Nur Adlina; Rahmad, Rohani Binti (Progress in Engineering Application and Technology, 2023)
Flow metres of the vortex type are used to measure the velocity of the flow of gases and liquids in a specific container, such as a pipeline, a tank, a chamber used in industry, or a natural source. Each has its own technology and way of working. Currently, the Vortex Flow Metre in UTHM employs a model Digital YEWFLO 040 with suffix codes DBLSS1-2D to measure the flow rate of pipeline steam starting at one bar and not exceeding five bars produced by the boiler operation. This study aims to simulate the Vortex Flow Metre model with a steam pipeline from 100 kPa to 500 kPa. The realistic geometry of the model was applied using the Solidworks software, which was used to produce the 3D modelling of the steam pipe with the Vortex Flow Metre. Meshes were made and a boundary condition was added to the model with the help of ANSYS Workbench software. In this study, there was also an experimental method used to get the actual mass flow rate data from the Vortex Flow Meter. The results of both the simulation and the experiment were compared and figured out. The results of the simulation show that as the pressure went up, so did the mass flow rate and this shows that the relationship between pressure and flow is linear. In the experiment, the steam pressure was controlled by the temperature relief valve in manual mode when the pressure gauge reached 3 to 5 bars. The results shows that in simulation the mass flow rate is greater compare to in the experiment. The difference between the simulation and experiment flow rate values is almost the same, which is 20%. According to the findings of this study is an acceptable range, also it is important to keep track of the mass flow rate data in order to enhance and improve the efficiency of steam itself.